Efficient Recycling of Crop Residue through biochar for better agriculture and environment - Datta, Debarati; Saxena, S C (Indian Farming, 2017)
Biochar is a solid material obtained from the carbonisation ofbiomass. Large varieties of biomass products can be used to produce biochar. It improves fertility and quality of poor soils, thus, reducing the need for fertilizer inputs and enhancing crop productivity, by transforming low value crop residue into potentially high value carbon source. Application of biochar has several environmental benefits including mitigation of greenhouse gas emission and long term carbon storage in soil. So, biochar can be an important tool to increase food security and cropland diversity inareas with severely depleted soils, scarce organic resources, andinadequate water and chemical fertilizer supplies in a sustainable way.